The dynamics behind private banking growth in Egypt - Doaa M. Salman Abdou; Yomna Alarabi (Future Business Journal, 2024)
Abstract The research investigates the determinants of private banks profitability in Egypt. The determinants are bank specific (liquidity, capital adequacy, bank size, asset structure, credit risk, and non-performing loans), industry-specific (industry concentration and banking industry development), and macroeconomics (economic growth and inflation). It is an empirical study applying a quantitative method for data analysis and the type of data is secondary data. The sample size of the research is 15 private banks on the Egyptian and the panel data for the research is 2013–2022. The multiple linear regression analysis using the Eviews 12 application as an analytical tool by applying generalized least squares model. The profitability of private banks, which is the dependent factor, is calculated by two measurements, Return on Assets and Return on Equity with ten determinants of profitability as independent variables. Results indicate that capital adequacy, economic growth bank size, and inflation has a positive significant effect on private banks profitability in Egypt. While NPL, liquidity and credit risk have significant negative effect on private banks profitability in Egypt. Based on the results recommendations are provided for bank management to maximize their profitability.